Adherence to anti-hypertensive medications and its determinants: A study among hypertensive stroke patients in a tertiary care government hospital of West Bengal - Adrija Ray; Tapobrata Guha Ray; Jyotirmoy Pal; Biman Kanti Ray; Debasish Sanyal; Souvik Dubey (Wolters Kluwer Medknow Publications, 2021)
There is a paucity of antihypertensive drug adherence studies among stroke patients in West Bengal. With an aim to identify antihypertensive drug adherence and its determinants, this descriptive cross-sectional study was conducted for 2 months among a calculated sample of 133 study participants using predesigned and pretested schedule, the metric "Proportion of days covered (PDC)," and the Morisky, Green, and Levine (MGL) Scale. Data were compiled and analyzed using SPSS software (version 20.0). Adherence rates were 31.6% and 44.4% based on the MGL scale and PDC method, respectively. Higher adherence was significantly associated with increased age (P = 0.006), higher literacy (P = 0.013), increased interval between diagnosis of hypertension and present symptom (P = 0.001), a greater gap between antihypertensive treatment initiation and present symptom (P = 0.003), receiving advice on regular drug intake (P = 0.000), and registered medical practitioner prescribing the medication (P = 0.007).